(untitled) (Revista de Ciências Agroveterinárias, 2010)
The aim of this study was characterize the profile of poultry eggs farms of Santa Catarina State, Brazil. A questionnaire was applied on poultry farmers from Sep/2006 to July/2007. Properties with more than 60 thousands chickens were minority in the State (4%), although they answer for great part of yield. Properties with up to 5 thousands chickens were the majority (52%), although they totalize only 6.5% of total chickens. Nearly 80% of the properties are closer from 10 km to town. The market that absorbs the eggs is regional. Half of the poultry farmers have internet access and do not intend to increase production. They also face great competition of fertile eggs and eggs from other States. Producers do not live based only on this activity. They also have no difficulty for marketing the eggs. Factors that affect small producers are not the same that affect the large ones. Nearly 70% of producers have no working capital for one production year and need credit to increase and modernize the production. The situation of egg producers from Santa Catarina State is fragile due to the competition with eggs originated from other States.